Employee Identification and Productivity Among Academic Staff of Nigerian Polytechnics - Abba, Halilu Dahiru; Anumaka, Ijeoma B.; Mugizi, Wilson (NIU Journal of Social Sciences, 2017)
The study investigated the relationship between employee identification and productivity of academic staff in polytechnics in Nigeria. The correlational study involved 285 respondents from six polytechnics. Data were collected using a self-administered a questionnaire whose validity and reliability was confirmed through Factor Analysis and Cronbach Alpha test. Descriptive analysis involved the use of means, while multiple regression was used to test the hypotheses. The results revealed that while group identification was an insignificant determinant of academic staff productivity while organisational identification was not. Thus, it was concluded that group identification was important for the performance of higher education institutions. Therefore, it was recommended that the leadership of higher institutions such as polytechnics should put in place mechanisms to promote group identification. Keywords: Academic Staff, Employee Identification, Group Identification. Organisational Identification, Polytechnics. Productivity.